Hidrops Fetalis dengan Kistik Higroma - Esfi Triana; Ori John (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2019)
Introduction: Fetal hydrops is excessive accumulation of fluid inside fetal body. Fetal hydrops can be presented with fetal and placental edema, ascites, pleural and/or pericardial effusion. In past years, most fetal hydrops was caused by severe fetal erythroblastosis related to Rhesus isoimmunization. In recent years, it mostly caused by other condition (non-immune fetal hydrops). Cystic hygroma was an etiology of fetal hydrops. Cystic hygroma was connected with chromosomal abnormalities. This case was presented a woman in her 21 weeks of gestational age with fetal hydrops and cystic hygroma suspected caused by chromosomal abnormality. This case report was highlighting the connection between fetal hydrops and cystic hygroma and the role of genetic evaluation to diagnose aneuploid.